REPRODUKSI WACANA METABO LAW DALAM PEMBENTUKAN STEREOTYPE FAT CHARACTER PADA ANIME JEPANG - Santi Andayani; Ni Made Savitri Paramita (IZUMI, 2018)
(Title: The Reproduction Of Metabo Law Discourse In Constructing Fat Characters Stereotype In Japanese Animes) Japanese government through Ministry of Health, Labor and Welfare (MHLW) in 2008 issued the Metabo Law regulation, which is the standard of medical and health guidance that is done specifically with the purpose to decrease the number of obesity which cause the metabolic syndrome. This regulation put the body of each individual to be open to the public. Using Foucault’s perception, this study look how Metabo Law works and how the reproduction of Metabo Law discourses constructing stereotype of fat character in Japanese anime. This study took data from 14 fat character in 13 anime, airing in 2008’s until 2015’s. To complete the data, interview were conducted on 5 Japanese about their understanding about Metabo Law. This study shows that with the normalization process using yearly general checkup and the reproduction of Metabo Law discourses, Japanese government successfully change the Japanese mindset and their behavior in maintained a healthy life style and to stay slim. The stereotype of the fat character that emerge as the product of reproduction of Metabo Law discourses is greedy, careless, cowardly, shy/ have low self-confident, and an otaku.   gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor